Acoustic analysis of clients’ expression of self-compassion, self-criticism, and self-protection within emotion focused therapy video sessions - Bailey, Ghazaleh; Halamová, Júlia; Vráblová, Viktória (Frontiers in Psychology, 2024)
All procedures performed in studies involving human participants were in accordance with the ethical standards of the institutional and/or national research committee and with the 1964 Helsinki declaration and its later amendments or comparable ethical standards.Written informed consent was obtained from all individual participants included in the study.In order to comply with the ethics approvals of the study protocols, data cannot be made accessible through a public repository. However, data are available upon request for researchers who consent to adhering to the ethical regulations for confidential data.